Amnibacterium flavum sp. nov., a novel endophytic actinobacterium isolated from bark of Nerium indicum Mill. Issue 1 (4th December 2018) - Tuo, Li; Yan, Xiao-Rui; Li, Fei-Na; Yang, Chao; An, Ming-Biao; Sun, Cheng-Hang
Abstract : A Gram-stain-positive, aerobic, short-rod-shaped, non-spore-forming actinobacterial strain, designated M8JJ-5 T, was isolated from a surface-sterilized bark of Neriumindicum Mill. collected from Guizhou, China, and investigated by a polyphasic approach to determine its taxonomic position. Strain M8JJ-5 T grew optimally without NaCl at 28 °C and at pH 7.0–8.0. Substrate mycelia and aerial mycelia were not formed, and no diffusible pigments were observed on the media tested. Phylogenetic analysis based on the 16S rRNA gene sequence showed that strain M8JJ-5 T was most closely related to the type strains of genus Amnibacterium, and shared highest 16S rRNA gene sequence similarity of 97.29 % to Amnibacterium kyonggiense KSL51201-037 T . The DNA G + C content of strain M8JJ-5 T was 68.6 mol%. The cell-wall peptidoglycan contained l -2, 4-diaminobutyric acid and MK-12, MK-11 were the major menaquinones. The predominant polar lipids were diphosphatidylglycerol, phosphatidylglycerol, an unidentified glycolipid, an unidentified phospholipid and an unidentified lipid, while the major fatty acids were iso-C16 : 0, anteiso-C15 : 0 and anteiso-C17 : 0 . On the basis of phylogenetic, chemotaxonomic and phenotypic data, strain M8JJ-5 T can be characterized to represent a novel species of the genus Amnibacterium, for which the name Amnibacterium flavum sp. nov. is proposed. The type strain is M8JJ-5 T (=KCTC 49089 T =CGMCC 1.16390 T ).